2020
DOI: 10.1155/2020/2087475
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Application of a 3D‐Printed Poly‐ε‐Caprolactone Cage Scaffold for Bone Tissue Engineering

Abstract: Poly-ε-caprolactone (PCL) is a promising synthetic material in bone tissue engineering (BTE). Particularly, the introduction of rapid prototyping (RP) represents the possibility of manufacturing PCL scaffolds with customized appearances and structures. Bio-Oss is a natural bone mineral matrix with significant osteogenic effects; however, it has limitations in being constructed and maintained into specific shapes and sites. In this study, we used RP and fabricated a hollow-structured cage-shaped PCL scaffold lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…Bone defects caused by various conditions, such as congenital malformation, trauma, tumor resection, and infection, not only cause great pain but also place tremendous pressure on healthcare systems [ 1 ]. Bone tissue engineering (BTE) emerging in recent decades now provides an option for the therapy of bone defects.…”
Section: Introductionmentioning
confidence: 99%
“…Bone defects caused by various conditions, such as congenital malformation, trauma, tumor resection, and infection, not only cause great pain but also place tremendous pressure on healthcare systems [ 1 ]. Bone tissue engineering (BTE) emerging in recent decades now provides an option for the therapy of bone defects.…”
Section: Introductionmentioning
confidence: 99%
“…The surface affinity of a scaffold with water and proteins influences biological responses to the scaffold. [39][40][41] Thus, water absorption and protein adhesion tests were carried out as part of the present study. In the water absorption test, Ap-CS absorbed more water than did CS (Figure 4A), suggesting that the apatite coating on Ap-CS increased the surface hydrophilicity of the scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the BMSCs–scaffold construct was cultured in vitro for 21 days before implantation, which makes it more conducive to the synthesis and accumulation of cartilage ECM, resulting in more mature structure and function, so that it responds more quickly to knee joint pressure after implantation. In addition, studies showed that surface modification of the PCL scaffold increases the adhesion, proliferation, and differentiation characteristics of seeded cells, which is an exploration direction for us to further optimize and modify the meniscus scaffold [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%